Teacher Voice in Cycles for Iterative Improvement - Carissa Maddox (Adult Education Research Conference, 2023)
Teachers in a mixed-method action research study of cycles for iterative improvement reveal that increased teacher voice would lead to stronger commitments and the likelihood of follow through.
Keywords: school improvement; collective commitments; teacher voice